A NOVEL RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF BERBERINE, QUERCETIN, AND PIPERINE IN AN AYURVEDIC FORMULATION - Sahani, Swati; Jain, Vandana (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to develop and validate a novel, simple, rapid, precise and accurate reversed-phase high performance liquid chromatographic (RP-HPLC) method for simultaneous quantitative estimation of berberine, quercetin, and piperine in Ayurvedic formulation. Methods: The chromatographic separation was achieved using a stationary phase C18 shim-pack (150 mm x 4.6 mm, 5Âµ) column and mobile phase consisted of acetonitrile: 0.04 M potassium dihydrogen phosphate buffer (pH 3.0 adjusted using orthophosphoric acid) in a ratio of 65:35 v/v, with a flow rate of 1 ml/min and UV detection at 255 nm. Results: The retention time of berberine, quercetin, and piperine were found to be 2.7, 3.0 and 6.3 min respectively. Linearity for berberine, quercetin, and piperine were found in the range of 12-28 Âµg/ml. All calibration curve showed good linear correlation coefficients (r2Ëƒ 0.999) within the tested ranges. Mean percent recoveries for berberine, quercetin, and piperine were found to be within the acceptance limits (98-120%). The percent relative standard deviation (% RSD) for precision was found to be less than 2% which indicates method is precise. Conclusion: The developed method is novel, simple, precise, accurate and can be used for quantitative analysis and quality control of the raw material as well as other commercial formulations containing these three markers.